(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1975)
Were randomly selected, 809 chickens for meat production in order to compose two groups named here “A” and “B” strains. After fastening for 14 hours, the birds were slaughtered in industrial condition. Then, 111 males and 111 females were selected at random from each strain and their live weight, eviscerated carcass weight and yield of this late were recorded. Based on live weight, the strain “B” yielded higher percentage of eviscerated carcass than strain “A”, although the heaviest carcass weights were obtained in strain “A”. Although heavier carcass weights were found in males, there no significant differences between sexes in relation to the carcass’ yield. Regression equations and coefficients of determination for the interrelation of live weight and carcass weight, were determined in relation to both sexes and strains. Data from giblets — gizzard, heart and liver — and legs, heads and necks were also studied and discussed.